Results of an Experimental Study of the Development of Pedagogical Reflection among Future Chemistry Teachers in Blended Learning Conditions - Kochubei, Olena; Sovhira, Svitlana; Dushechkina, Nataliia (Educological discourse, 2025)
The article reveals the results of a study focused on the development of pedagogical reflection among future chemistry teachers in a blended learning environment. In the context of modern challenges and the digital transformation of education, the ability of a teacher to reflect on their professional activity, critically assess pedagogical decisions, and consciously improve their teaching strategies becomes a key component of their professional competence. The relevance of the research is determined by the need to develop effective pedagogical conditions for forming reflexive skills among students of natural science specialties, particularly those specializing in chemistry, who work with complex scientific material and require developed analytical thinking. The aim of the study was to test the effectiveness of specially created pedagogical conditions that promote the development of pedagogical reflection in future chemistry teachers in blended learning. The methodological basis was the systemic, personally oriented, competency-based and activity-based approaches. The experimental study was conducted in two groups: control and experimental. During the formative stage, the experimental group was introduced to the use of digital platforms (Google Classroom, Padlet), keeping reflective diaries, modeling pedagogical situations, self- and mutual assessment. The experiment demonstrated that systematic use of reflection-focused practices — such as reflective diaries, case discussions, self-assessment, and digital tools (Padlet, Google Classroom) — significantly increased students’ reflective competence. In the experimental group, the number of students with a high level of pedagogical reflection increased from 9 % to 45 %, while the proportion of students with a low level decreased from 53 % to 14 %. These quantitative results were supported by qualitative improvements in students’ ability to critically analyse their pedagogical experiences, justify their educational choices, and formulate alternative solutions to teaching situations. The novelty of the study lies in integrating digital technologies with reflective strategies within the professional training of chemistry teachers, an area previously underexplored in pedagogical science. The study also identifies specific conditions that contribute to sustainable development of reflection skills in blended learning environments.